Georgia - Kozlowski, Ken (The journal of offender monitoring, 2020)
Brings together in one place Georgia statutory provisions citing electronic monitoring as either a sentencing option or requirement. Covers sentencing provisions, the use of electronic monitoring in probation and parole, and tampering and escape. (Volume 33 Number 1 includes the complete federal and all fifty state statutes.)